Food reinforcement partially mediates the effect of socioeconomic status on body mass index. (11th June 2013) - Lin, Henry; Carr, Katelyn A.; Fletcher, Kelly D.; Epstein, Leonard H.
<x xml:space="preserve">Abstract</x> Objective Low socioeconomic status (low SES), as defined by income or educational attainment, has been associated with obesity in industrialized nations. Low SES persons have limited resources and may experience food insecurity that increases food reinforcement. Food reinforcement has been positively related to energy intake and weight status, and increased food reinforcement may explain the higher prevalence of obesity among low SES individuals who have restricted access to low‐energy‐dense foods and nonfood reinforcers. Design and Methods Annual household income, highest education level completed and food reinforcement in 166 adults of varying body mass index (BMI, kg m−2) was measured. Results Multivariate linear regression analyses controlling for age, sex, minority status, session hunger, and the reinforcing value of nonfood alternatives showed that household income was related to food reinforcement (P = 0.048) and BMI (P = 0.019), and that food reinforcement was related to BMI (P = 0.0017). Path analyses revealed a significant indirect effect of household income on BMI through food reinforcement, suggesting that the relationship between lower household income and greater BMI was mediated in part by increased food reinforcement. A similar pattern of results was observed when education level was used as the proxy for SES. Conclusions These findings support the hypothesis that deprivation and restricted food choice associated with low SES enhance food reinforcement, increasing the risk for obesity.